A Field Measurement of Noise Comfort Classroom in Xaverius Pringsewu Senior High School - Ai Siti Munawaroh; Christina Christina (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2021)
A school is a place where all learning activities are carried out by students. In learning activities in the classroom, it must meet a good standard of comfort, especially the noise factor. Classroom noise can be caused by external and internal factors. The audial comfort level for classrooms is standard 55 Dba. The purpose of this study was to determine and analyze the comfort level of noise in the classroom at Xaverius Pringsewu High School. The research methods were field measurement using sound level meter. In addition survey was conducted on building users with questionnaire to know about perception of audio comfort.The classrooms studied have a classroom design where the wall vents of the two classes have different heights. With a different ventilation design, it will certainly affect the noise conditions in the classroom. The study resulted that classroom RK 1 was noisier than the classroom RK 2 due to the different class design where the classroom RK 1 had wide ventilation on the wall, while the classroom RK 2 had a closed room with vents on the door and window.